Diagnostic value of 18F-FDG PET/CT in discriminating between benign and malignant lesions of the ribs. Issue 27 (8th July 2022) - Choi, Sunju; Kim, Yong-il; Lee, Geun Dong; Choi, Sehoon; Kim, Hyeong Ryul; Kim, Yong-Hee; Kim, Dong Kwan; Park, Seung-Il; Ryu, Jin-Sook
Abstract : Purpose: Imaging biomarkers for rib mass are needed to optimize treatment plan. We investigated the diagnostic value of metabolic and volumetric parameters from 18 F-fluorodeoxyglucose (FDG) positron-emission tomography/computed tomography (PET/CT) in discriminating between benign and malignant lesions of the ribs. Patients and methods: Fifty-seven patients with pathologically proven diagnosis of rib lesions were retrospectively enrolled. The size of rib lesions, the maximum, mean, and peak standardized uptake value (SUVmax, SUVmean, SUVpeak), tumor-to-background ratio (TBR), metabolic tumor volume (MTV), and total lesions glycolysis (TLG) were measured. The FDG uptake patterns (segmental and discrete) and CT findings (soft tissue involvement and fracture) were also reviewed. Results: Among the multiple parameters extracted from PET/CT, the MTV of malignant lesions was significantly higher than that of benign lesions (median; 4.7 vs 0.2, respectively, P = .041). In receiver operating characteristics curve analysis, MTV had the largest area under curve of 0.672 for differentiating malignant from benign lesions. For identifying malignant lesions, an MTV threshold of 0.5 had a sensitivity of 85.0%, specificity of 47.1%, positive predictive value of 79.1%, negative predictive value of 57.1%, and accuracy of 73.7%. The presence of adjacent soft tissue involvement around rib lesions showed a significant association with malignancy (odds ratio = 6.750; 95% CI, 1.837–24.802, P = .003). Conclusions: The MTV is a useful PET/CT parameter for assisting in the differential diagnosis of suspected malignant lesions of the ribs. CT finding of adjacent soft tissue involvement around rib was significantly associated with malignant lesions of the ribs.